Effectiveness of aluminum electrode in reducing bod, cod, ammoniac, and chromium in leather tannering waste with the electrocoagulation process - Dwi Astuti (Science Midwifery, 2022)
Tanning industry skin use ingredient chemical and water in amount which so much This process produces liquid waste containing various organic substances from ingredient raw and substance chemical from additional materials used During process tanning. This study aims to determine the efficiency of the electrocoagulation method in reducing the parameters BOD, COD, ammonia, and chromium. A sample of 100 liters of leather tanning waste water used is put into a grease trap and flowed into an electrocoagulation bath in which electrodes (3 cathodes and 3 anodes) have been arranged. The electrocoagulation process lasted for 60 minutes. Parameters of wastewater quality examined include BOD (Biological Oxygen Demand), COD (Chemical Oxygen Demand), ammonia, and total chromium. The method for measuring the quality parameters of tannery wastewater uses the appropriate Indonesian National Standards. The results of the measurements will be analyzed descriptively by comparing the results with the standards of the Minister of Environment of the Republic of Indonesia Number 5 of 2014 concerning Quality Standards for Tannery Wastewater. After the electrocoagulation process is complete, then the effectiveness is calculated in percent (%). The effectiveness of the electrocoagulation process in reducing the levels of parameters from the highest percentage was total chromium (62.01%); COD (58.29%); BOD (52.52%); and ammonia (42.79%). The electrocoagulation process is quite effective in reducing the levels of tannery wastewater quality parameters.